Harnessing implementation science to integrate ambulatory assessment data into clinical practice. - Scholten, Saskia; Burger, Julian; Hall, Mila; Hehlmann, Miriam; Piccirillo, Marilyn L. (Psychotherapy Research, 2026)
The article focuses on the integration of Ambulatory Assessment (AA) data into clinical practice, specifically through the Awaken Digital Guide, a Transdiagnostic Network-Informed Personalized Treatment for Eating Disorders. It emphasizes the importance of implementation science and the Consolidated Framework for Implementation Research (CFIR) in understanding the barriers and facilitators to adopting this data-driven approach. Key challenges include clinician and client concerns about the feasibility and acceptability of AA, as well as systemic issues within healthcare settings. The authors advocate for research-practice partnerships to address these barriers and enhance the effectiveness of AA in delivering personalized care.